1998
DOI: 10.1111/j.1574-695x.1998.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis patients have T-cells with reduced responsiveness to common mycobacterial antigens

Abstract: Heparinised blood samples were obtained from 20 patients with chronic plaque psoriasis and from 13 age-matched healthy controls. After preliminary titration, mononuclear cells separated over Ficoll-Tryoson were cultured for 5 days with 10 microg ml(-1) of 15 mycobacterial preparations, or with pokeweed mitogen and concanavalin A. Stimulation indices were determined for each reagent and means were determined for patients and controls. Results for patients showed a striking reduction of responsiveness to mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Upper respiratory tract infections have been implicated in the development of psoriasis, and increasing evidence points to a triggering role for bacterial superantigens in providing the T-cell activating stimulus [6,7]. We have shown lymphocytes of psoriasis patients to respond less to group i, common mycobacterial antigens, than do healthy persons [8], suggesting an abnormal response to environmental mycobacteria which may be an aetiological factor in the disease.…”
Section: Introductionmentioning
confidence: 67%
“…Upper respiratory tract infections have been implicated in the development of psoriasis, and increasing evidence points to a triggering role for bacterial superantigens in providing the T-cell activating stimulus [6,7]. We have shown lymphocytes of psoriasis patients to respond less to group i, common mycobacterial antigens, than do healthy persons [8], suggesting an abnormal response to environmental mycobacteria which may be an aetiological factor in the disease.…”
Section: Introductionmentioning
confidence: 67%
“…6 Some authors have suggested an abnormal lymphocytic response to environmental mycobacteria as an etiologic factor. 7 However, the role of mycobacterial infection has not been conclusively proven.…”
Section: Discussionmentioning
confidence: 99%
“…However, a possible reason is that patients with psoriasis have an associated reduced T cell responsiveness to mycobacterium antigens. 149 Furthermore, dendritic cells and macrophages have been shown to be increased in the skin of patients with psoriasis underoing M. vaccae therapy, with an increased production of IL-10. 143 Since IL-10 is an immunosuppressing cytokine, stimulating immunity to mycobacterium with increased IL-10 may alter the immune balance to favor psoriasis clearance.…”
Section: Potential For Vaccine and Immunotherapy In Psoriasismentioning
confidence: 99%